The Flexibility of the “F” Word (Language Circle: Journal of Language and Literature, 2021)
The “f” word (fuck) cannot be separated from its taboo nature. This can reveal more deeply about its use which can be found every day that the “f” word is not always used in negative terms and may be useful to enrich the knowledge about the characteristics of the “f” word and to reduce the stigma about it that it has more than negative purpose in expressing emotions. This research would also clarify the reasons for the versatility of the “f” word itself because of the kind that can be used to convey the sense of a specific emotional situation. This study was created because of the shortcomings that the previous study had; Horvat (2016), Jay and Janschewitz (2008), and Pluszczyk (2015) who have not studied the function of the “f” word in detail. So the motivation is created with documentation technique and applying the framework of Shiedlower (1999) and Wang (2013) to further discuss that the “f” word can be flexible in terms of word elements and their function in this study. The results have 6 different types of word element and 4 functions of “f” word swearing